Monochromatic blue light enhances crocin and picrocrocin content by upregulating the expression of underlying biosynthetic pathway genes in saffron (Crocus sativus L.) - Moradi, Shirin; Kafi, Mohsen; Aliniaeifard, Sasan; Moosavi-Nezhad, Moein; Pedersen, Carsten; Gruda, Nazim S.; Salami, Seyed Alireza (Frontiers in Horticulture, 2022)
Saffron quality is determined by the content of three apocarotenoids, including crocin, picrocrocin, and safranal, giving saffron culinary, industrial, and medical importance. The level of these secondary metabolites is also affected by environmental factors such as light, which play a pivotal role in regulating plants' signaling pathways. In this study, we investigated the effects of different ratios of blue (B) to red (R) and white (W) light on physiological, biochemical, and molecular responses of saffron in the flowering stage. Flowers' morphological properties were improved in plants grown under monochromatic B light. The highest content of total carotenoids, anthocyanins, and flavonoids was detected in plants grown under a high proportion of B light. The highest crocin content, especially the trans- crocetin ester isomer, was recorded in monochromatic B light-grown plants. However, the highest picrocrocin content was in both monochromatic R- and B light-grown plants. The highest safranal content was detected in plants grown under a high proportion of R light. Transcriptome analysis of secondary metabolism pathways showed that the transcript level of the genes was highly correlated with the content of the target metabolites. Monochromatic B light upregulated the expression of genes involved in crocin production (CsCCD2, CsALDH31l, and CsUGT2). However, the expression of CsUGT709G1, which involves in picrocrocin and safranal pathways, was upregulated in plants grown under a high ratio of R light and W lights. In conclusion, monochromatic B light enhances the flowering rate, crocin (trans-crocetin ester), and picrocrocin content, which increases the quantity and quality of saffron products under controlled conditions.